2017
DOI: 10.1038/s41598-017-07407-1
|View full text |Cite
|
Sign up to set email alerts
|

Antidepressant-like effects and cognitive enhancement of Schisandra chinensis in chronic unpredictable mild stress mice and its related mechanism

Abstract: The aim of this study was to evaluate whether Schisandra chinensis extract (SCE) administration influences chronic unpredictable mild stress (CUMS)-induced depression and cognitive impairment, and explores underlying mechanisms. Sucrose preference test (SPT) and forced swimming test (FST) were used for assessing depressive symptoms, and Y-maze, Morris water maze were used for evaluating cognition processes. The results showed that CUMS (4 weeks) was effective in producing both depression and memory deficits in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
48
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 58 publications
(51 citation statements)
references
References 56 publications
3
48
0
Order By: Relevance
“…This study assessed the time courses of different behavioral, biochemical, and molecular parameters in three commonly used rodent depression models. Consistent with most of the literature (Gong et al, ; He et al, ; Yan et al, ), the UCMS model showed depressive‐like behavior and hyperlocomotion from the third week, as well as anxiety‐like behavior at the fifth week. The CORT model demonstrated depressive‐like behaviors and anxiolytic‐like behaviors from the third week, but no differences in locomotor activity in accordance with previous literature (Rosa et al, ).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…This study assessed the time courses of different behavioral, biochemical, and molecular parameters in three commonly used rodent depression models. Consistent with most of the literature (Gong et al, ; He et al, ; Yan et al, ), the UCMS model showed depressive‐like behavior and hyperlocomotion from the third week, as well as anxiety‐like behavior at the fifth week. The CORT model demonstrated depressive‐like behaviors and anxiolytic‐like behaviors from the third week, but no differences in locomotor activity in accordance with previous literature (Rosa et al, ).…”
Section: Discussionsupporting
confidence: 88%
“…The UCMS model includes chronic depression by presenting unpredictable stress stimuli (Gupta et al, ) such as multiple, randomly scheduled food and water deprivation, overnight illumination, cage tilting, and other similar stressors that may be associated with human patients (Boyle et al, ). In most published studies, the UCMS model induced depression for 2–4 weeks, but some have been tested for up to eight weeks (He et al, ; Wu et al, ; Xia et al, ; Yan et al, ; N. Zhang et al, ). High levels of serum cortisol, related to elevated hypothalamo‐pituitary‐adrenal (HPA) axis activity, can be associated with depression.…”
Section: Introductionmentioning
confidence: 99%
“…The downregulation of norepinephrine (NE), and serotonin (5-hydroxytryptamine, 5-HT) levels and the decrease of synaptic content cause depression [36,37]. Brain derived neurotrophic factor (BDNF) controls the development of neuronal function and becomes ineffective in neurodegenerative disorders such as depression [38]. The ionized calcium binding adaptor molecule 1 (IBA-1) is responsible for the microglia activation in hippocampus and cortex [39].…”
Section: Neurodegenerative Diseasementioning
confidence: 99%
“…Yan et al reported that SCF could improve a depression-like emotional state and associated cognitive deficits in mice with chronic unpredictable mild stress (CUMS). The mechanism was proven to regulate BDNF expression in the hippocampus as well as upregulate the TrkB/CREB/ERK and PI3K/Akt/GSK-3β pathways [ 22 , 23 ]. Moreover, Yuan et al reported that nigranoic acid (SBB1, 3,4-secocycloartene triterpenoid) manifested beneficial effects in terms of enhancing mental and intellectual functions by increasing BDNF and c-fos expression in NGF-differentiated PC12 cells [ 53 ].…”
Section: Modulation Of Bdnf Related Pathwaysmentioning
confidence: 99%